(untitled) (Academicia Globe: Inderscience Research, 2023)
This article is modern in the world Russian on request common the concept gives In the article, Russian language in the world the most a lot used from languages one as is introduced . In the article Russian language , different in the fields used , online teaching platforms using ease and Russian language of learning importance about data is given In the article exactly , Russian language of learning personal , corporate and international organizations with cooperation to do opportunities will be lit. Article modern in the world Russian language of learning importance and in our country language of learning make it easier shows . In the article given information , Russian language of learning different in the fields benefits shows and this the language of learning easy and efficient to be for methods and own technologies into takes Modern in the world Russian language still of the world the most important from their languages is one This language is Russian the speaker people the number and Russia Federation another many countries being trained because of , open pointer communication of opportunity high level to be because of big important have.